Perencanaan ruang terbuka publik di Desa Dasan Cermen, Kota Mataram untuk mendukung aktivitas budaya lokal - Fitrasari, Mita Putri; Sugianthara, Anak Agung Gede; Yusiana, Lury Sevita (Jurnal Arsitektur Lansekap; Vol.4, No.1, April 2018DO - 10.24843/JAL.2018.v04.i01.p02, 2018)
Planning of public open space in Dasan Cermen Park, Mataram City to support local cultural activities. Mataram city has experienced development rapidly that causes the need of builded space is increased so that the quality of the environment is getting lower, so it needs the existence of public open space. In addition to having ecological functions, the existence of public open space also has a socio-cultural function as a place of social interaction and describes the local cultural expression. Based on these problems, it is necessary to have a public open space planning in the form of a park that can describe the local cultural expression. The purpose of this research is to plan the park in accordance with the local cultural identity of Mataram city. This research used survey method with observation technique, interview, questionnaire distribution and literature study. Planning refers to systematic planning method. The concept applied is the preservation of local culture. The final result of this research is planning of public open space in Dasan Cermen Mataram City which is divided into three spaces, such as conservation space, social space and cultural space. Further research is needed to design of public open space in Dasan Cermen Mataram City and attention to aspects of public open space management.